Neurocognitive impairment in females with breast cancer treated with endocrine therapy and CDK4/6 inhibitors: a pharmacovigilance study using the World Health Organization’s database - Prevost, Rachel; Chretien, Basile; Minoc, Elise-Marie; Dolladille, Charles; Da-Silva, Angélique; Nehme, Ahmad; Joly, Florence; Lelong-Boulouard, Véronique; Bastien, Etienne (Frontiers in Pharmacology, 2023)
1 Abstract 1.1 Importance Endocrine therapies (ETs) and inhibitors of the cycline-dependent-kinase-4/6 (iCDK4/6s) are a standard treatment in breast cancer. However, data on potential neurocognitive impacts remain inconsistent for ET and are scarce for iCDK4/6s. 1.2 Objective To evaluate if ET and iCDK4/6s are associated with neurocognitive impairment (NCI). 1.3 Methods We used observational, real-word cases of NCI from the World Health’s Organization database VigiBase® to perform disproportionality analysis. Cases were defined as any symptom of NCI in females treated with ETs or iCDK4/6s. The study period was from the date of the first adverse event reported in VigiBase® with iCDK4/6s (January 1st, 2014) to the date of data extraction (March 16th, 2022). In our primary analysis, we calculated the reporting-odds-ratio (ROR) adjusted for age to identify a potential association between NCI and individual ETs in isolation or in combination with iCDK4/6s. We also performed subgroup analyses by NCI class. 1.4 Results We respectively identified 2.582 and 1.943 reports of NCI associated with ETs and iCDK4/6s. NCI was significantly associated with each ET (anastrozole: n=405, aROR=1.52 [95% CI: 1.37-1.67]; letrozole: n=741, aROR=1.37 [95% CI: 1.27-1.47]; exemestane: n=316, aROR= 1.37 [95% CI: 1.22-1.53]; tamoxifen: n=311, aROR=1.25 [95% CI: 1.12-1.40]; fulvestrant: n=319, aROR=1.19 [95% CI: 1.06-1.33]) and only with palbociclib for iCDK4/6s (n=1542, aROR=1.41 [95% CI: 1.34-1.48]). 1.5 Conclusions These findings suggest that in females treated for breast cancer, all ETs may be associated with NCI. However, amongst iCDK4/6s, NCI may be specific to palbociclib. NCI most frequently involved learning and memory as well as language. Neurocognitive impact of treatments requires better consideration and management.